2021
DOI: 10.1177/17531934211061437
|View full text |Cite
|
Sign up to set email alerts
|

The anatomy of the anconeus nerve redefined

Abstract: The anconeus nerve is the longest branch of the radial nerve and suitable as a donor for the neurotization of the axillary nerve. The aim of this study was to map its topographical course with reference to palpable, anatomical landmarks. The anconeus nerve was followed in 15 cadaveric specimens from its origin to its entry to the anconeus. It runs between the lateral and the medial head of the triceps before entering the medial head and running intramuscularly further distal. Exiting the muscle, it lies on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
1
0
0
Order By: Relevance
“…Maniglio et al [21] revised the anatomy of the anconeus branch in 15 elbows, and their results are well comparable to our topographical results in a larger collective. The anconeus branch separated from the radial nerve at mean 16.4 cm from the lateral epicondyle, which is similar to our mean of 17.7 cm measured from the olecranon.…”
Section: Discussionsupporting
confidence: 87%
“…Maniglio et al [21] revised the anatomy of the anconeus branch in 15 elbows, and their results are well comparable to our topographical results in a larger collective. The anconeus branch separated from the radial nerve at mean 16.4 cm from the lateral epicondyle, which is similar to our mean of 17.7 cm measured from the olecranon.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, there were no mentions of notable anconeus denervation nor functional deficits in the retrospective series of PCNF-BrEpi surgical denervation by Rose et al and Dellon, and neither reports explicitly identified or isolated the PCNF-BrA as part of their surgical techniques [ 1 , 12 ]. In addition, there is a discrepancy regarding the motor innervation to the anconeus, as described by Maniglio et al, who describe the anconeus nerve (a direct branch off the trifurcation point of the distal radial nerve) to supply the motor innervation to the anconeus and do not mention or identify PCNF-BrA [ 13 ]. Provided these inconsistencies regarding the motor supply to the anconeus, and given the anconeus is an accessory muscle for elbow extension, the potential denervation by inadvertent PCNF-BrA injury likely has minimal-to-no functional consequence.…”
Section: Discussionmentioning
confidence: 99%